2010
DOI: 10.1681/asn.2009121210
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Kidney Function Decline Associates with Mortality

Abstract: The effect of rate of decline of kidney function on risk for death is not well understood. Using the Department of Veterans Affairs national databases, we retrospectively studied a cohort of 4171 patients who had rheumatoid arthritis and early stage 3 chronic kidney disease (CKD; estimated GFR 45 to 60 ml/min) and followed them longitudinally to characterize predictors of disease progression and the effect of rate of kidney function decline on mortality. After a median of 2.6 years, 1604 (38%) maintained stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
184
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(201 citation statements)
references
References 42 publications
8
184
5
1
Order By: Relevance
“…Indeed, according to this study, GPs can be considered as a reference of care for patients in stage 3a without asking for nephrology consultation, because these patients have the same risk as the reference group (Table 4). The clinical characteristics of our patients with CKD stage 3a, in fact, show low prevalence for the main cardiorenal risk factors (i.e., albuminuria, anemia, diabetes, and CAD) with respect to more advanced stages of CKD (3b-5), and therefore, their profile is compatible with nonprogressive CKD (26)(27)(28)(29)(30). However, the suggestion of referring patients with CKD when eGFR is ,45 ml/min per 1.73m 2 is in agreement with the timing of onset of CKD-related metabolic complications (31).…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, according to this study, GPs can be considered as a reference of care for patients in stage 3a without asking for nephrology consultation, because these patients have the same risk as the reference group (Table 4). The clinical characteristics of our patients with CKD stage 3a, in fact, show low prevalence for the main cardiorenal risk factors (i.e., albuminuria, anemia, diabetes, and CAD) with respect to more advanced stages of CKD (3b-5), and therefore, their profile is compatible with nonprogressive CKD (26)(27)(28)(29)(30). However, the suggestion of referring patients with CKD when eGFR is ,45 ml/min per 1.73m 2 is in agreement with the timing of onset of CKD-related metabolic complications (31).…”
Section: Discussionmentioning
confidence: 76%
“…Other community-based approaches have been successful, such as the integrated model of care using community health workers for Maori and Pacific Islander participants with CKD and hypertension that resulted in improved BP control and albuminuria; these are key to developing targeted management approaches (30). In addition, incorporation of the rate of eGFR decline into the CKD definition may help identify high-risk patients (31). Longer-term follow-up of this cohort will further inform these clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous work, in which adjustments were made for either the first or last eGFR in the antecedent period, we found a U-shaped relationship between eGFR slope and subsequent ACM risk. 11,[13][14][15][16] Direct, quantitative comparison between the results of these investigations and our own investigations are hampered by different indices of renal function change, different antecedent periods, and the use of rates, in some studies, rather than HRs to quantify mortality risk. However, Turin et al 12 found adjusted HRs for ACM of 1.14 and 1.68 for 4-ml/min per 1.73 m 2 per year declining and increasing slopes, respectively, compared with subjects with a stable eGFR value in a Canadian population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A surprising finding in previous studies was that an increase in eGFR was associated with an increased risk of mortality. Whether these observations are generalizable is uncertain, because they were on the basis of data from single centers 13,14 and/or cohorts with mean baseline eGFR values of $50 ml/min per 1.73 m 2 . [11][12][13][14][15][16] Improvement in eGFR in a CKD population might show different associations with mortality than that in a general population cohort.…”
mentioning
confidence: 99%